Photovoltaic monitoring system for Auger Muons and Infill for the Ground Array - Angel Cancio Montbrun (Energy Science & Engineering, 2018)
Abstract This study is devoted to characterizing the operation of the entire photovoltaic system installed in one of the Auger Muons and Infill for the Ground Array (AMIGA) stations, a complimentary detector for the Pierre Auger Observatory, the largest cosmic‐ray air shower array in the world, 3000 km2, powered exclusively by solar energy. To understand charge and discharge cycles, the whole system behavior under different climatic conditions and to determine its limitations, the design of a new prototype for monitoring the whole system online is a fundamental part of this contribution. Also, it is demonstrated that the configuration of solar charge controllers in parallel is able to manage panels of different powers and brands and that the monitoring system allows analyzing periods with adverse weather conditions.